Prevalence and Long‐Term Survival After Coronary Artery Bypass Grafting in Women and Men With Heart Failure and Preserved Versus Reduced Ejection Fraction - Sun, Louise Y. (J Am Heart Assoc, 2018)
BACKGROUND: Heart failure (HF) with reduced ejection fraction (rEF) is a widely regarded prognosticator after coronary artery bypass grafting. HF with preserved ejection fraction (pEF) accounts for up to half of all HF cases and is associated with considerable morbidity and mortality in hospitalized cohorts. However, HFpEF outcomes have not been elucidated in cardiac surgical patients. We investigated the prevalence and outcomes of HFpEF and HFrEF in women and men following coronary artery bypass grafting. METHODS AND RESULTS: We conducted a retrospective cohort study in Ontario, Canada, between October 1, 2008, and March 31, 2015, using Cardiac Care Network and Canadian Institute of Health Information data. HF is captured through a validated population‐based database of all Ontarians with physician‐diagnosed HF. We defined pEF as ejection fraction ≥50% and rEF as ejection fraction <50%. The primary outcome was all‐cause mortality. Analyses were stratified by sex. Mortality rates were calculated using Kaplan–Meier method. The relative hazard of death was assessed using multivariable Cox proportional hazard models. Of 40 083 patients (20.6% women), 55.5% had pEF without HF, 25.7% had rEF without HF, 6.9% had HFpEF, and 12.0% had HFrEF. Age‐standardized HFpEF mortality rates at 4±2 years of follow‐up were similar in women and men. HFrEF standardized HFpEF mortality rates were higher in women than men. CONCLUSIONS: We found a higher prevalence and poorer prognosis of HFpEF in women. A history of HF was a more important prognosticator than ejection fraction. Preoperative screening and extended postoperative follow‐up should be focused on women and men with HF rather than on rEF alone.